Caracterização físico-química de espécies de madeiras do bioma amazônico para a preservação ambiental - Faita, Jéssica Rosa [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
The exhaustion of fossil fuels, non-renewable sources, has motivated the search for the use of renewable sources and with this, the efficient use of biomass. Brazil, which holds 69% of the Amazon Biome, is home to numerous species of plants and animals, and needs to know its flora more deeply in order to preserve the forests that face high rates of deforestation. In this way, the present study aims to perform the physicochemical characterization of some species of wood from the Amazon Biome to collaborate with information for the formation of a reference database in the protection of the environment, prevention and control of forest fires . The characterization evidenced the variation of moisture content, ashes, extractives, cellulose, hemicellulose and lignin among the species, confirming that the composition of the wood depends on factors such as age of wood, climate, region and climate. Woods with higher ash content are less susceptible to ignition and, undesirable for use in furnaces, and samples presented low values compared to other lignocellulosic materials. The high moisture content, linked to the amount of water in the woods, acts as a fire protection. The coloration of the analyzed wood presented strong interaction with the extractive content, the darker ones presented higher extractive content than the clear ones. The contents of cellulose, hemicellulose and lignin were similar to those found in the literature, in ratios ranging between approximately 40:30:30 and / or 50:20:30, respectively. These results contribute to the knowledge of the main characteristics of wood most commonly found in the Amazonian biome and is of great value for combating the burning and the sustainable use of these biomasses for the consolidation of a network of protection and maintenance of this ecosystem

A exaustão dos combustíveis fósseis, fontes não-renováveis, tem motivado a busca pela utilização de fontes renováveis e com isso, o uso eficiente da biomassa. O Brasil, detentor de 69% do Bioma da Amazônia, abrigando inúmeras espécies de plantas e animais, necessita conhecer, de forma mais profunda sua flora a fim de preservar as florestas que enfrentam altas taxas de desmatamento. Desta forma, o presente estudo tem como objetivo realizar a caracterização físico-química de algumas espécies das madeiras do Bioma da Amazônia para colaborar com informações para a formação de uma base de dados de referência na proteção do meio ambiente, prevenção e controle de incêndios florestais. A caracterização evidenciou a variação de teores de umidade, cinzas, extrativos, celulose, hemicelulose e lignina entre as espécies, confirmando que a composição da madeira depende de fatores como idade da madeira, clima, região e clima. Madeiras com maior teor de cinzas são menos suscetíveis à ignição, e, indesejados para utilização em fornos e, as amostras, apresentaram valores baixos em comparação à outros materiais lignocelulósicos. O alto teor de umidade, ligado a quantidade de água nas madeiras, age como proteção ao fogo. A coloração das madeiras analisadas apresentou forte interação ao teor de extrativos, as mais escuras apresentaram maior teor de extrativos que as mais claras. Os teores de celulose, hemicelulose e lignina foram similares aos encontrados na literatura, em proporções que variam entre aproximadamente 40:30:30 e/ou 50:20:30, respectivamente. Estes resultados contribuem para conhecimento das principais características de madeiras mais comumente encontradas no bioma amazônico e é de grande valia para o combate às queimadas e o uso sustentável dessas biomassas para a consolidação de uma rede de proteção e manutenção deste ecossistema
Physical-chemical characterization of wood species in the biome for environmental preservation
Keywords: Biomassa; Madeira - Proteção contra o fogo; Sustentabilidade; Biomass